NOWADAYS: THE ROLE OF INTERNET FOR PROPAGATION AND PROLIFERATION OF MUSIC - Mittal, Deepak Kumar (International Journal of Research -GRANTHAALAYAH, 2015)
In present day internet play a very important role for propagation and proliferation of music in India and world-wide. With the help of internet media we can get each and every information about the music at home. Many websites and softwares are available on internet browsing for music searching, watching, listening, reading and learning. Google search are best source for searching and type documents of music, YouTube (youtube is a video-sharing website), Skype (Skype is a tele communications application software that specializes in providing video chat and voice calls from computers via the Internet, Online radio (All major Indian and others FM radio stations ready for you to enjoy music and much more), E-Journals (Electronic journals are scholarly journals or intellectual magazines that can be accessed via electronic transmission. In practice, this means that they are usually published on the Web), Online and Downloading websites, Social network websites (for exchange messages, post status updates and photos, share videos and receive notifications when others update their profiles, Marketing websites for purchasing music products and accessories